Impact of a growing population in agricultural resource management: Exploring the global situation with a micro-level example - Karim, A.H.M Zehadul (Canadian Center of Science and Education, 2012)
A decade ago, David Pimentel and his associates (1998) reported to us that that at least ten million hectare of arable land is now being eroded and also abandoned throughout the world every year and consequently to compensate such loss, a huge amount of replacement is claimed from forest and other sources for agriculture and human settlement. In the mean time, world population has now exceeded 6 billion in the year 1999, and the projected data indicate that it is going to be almost 9 billion within the range of next 40 years. Accordingly, the demographers and environmentalists for that reason have come up with raising issues that the main challenges for environmental management throughout the world is now to determine our planet’s capacity to sustain such a huge amount of burgeoning human population. The paper thus assesses specifically the impact of growing population on agricultural resource-base around the world creating depressing pressure on sustainable environmental management. To exemplify such a trend of agricultural land use, the paper incorporated a detailed example from an ethnographic case study on indigenous land-use practices and the experiences associated with modern cultivation for adapting to an adverse situation caused by the severe impact of a growing population in the agricultural sector in rural Bangladesh.